Impact of introducing low lift pump on improving income of farm households in some areas of Bhola district in Bangladesh - Majumder, MK; Rahman, MS (Journal of the Bangladesh Agricultural University, 2012)
This study focuses the impact of low lift pump (LLP) on farm income and cropping patterns followed by the selected farmers in Bhola district. A random sampling technique was used for the study. Primary data were collected from 60 LLP users from January to March, 2010 through two set of pre-tested questionnaires. Descriptive statistics and profit function were used in the study. Most of the farmers are well experience in farming. The average age of the household head is 47 for owner, 45 for tenant, 44 for owner cum tenant and 41 for LLP owners. The average educational level is 6 for owner, 4 for cash tenant, 5 for owner cum tenant and 5 for LLP Owners. Household size is the largest for cash tenant which is 5.36. Mug Fallow - B.Aman was the main cropping patterns before using LLP and it was 39.22%. On the other hand, Boro Fallow -T.Aman was the main cropping pattern after introducing LLP and it was 53.22% in the study area. The income increased in all categories of farmers due to the introduction of LLP. Cash tenant earned more and owner cultivators earned less among the farmers categories. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11035 J. Bangladesh Agril. Univ. 9(2): 233240, 2011